Characteristics of Nominal Phrases with the Term Cell in Natural Sciences - Jakoša, Suzana; Glavač, Damjan; Stramljič Breznik, Irena (Slavia Centralis, 2022)
The article presents the term cell, which is shared by related and unrelated professional fields after the expansion of the original meaning of the word cell. The share of concepts with which it is connected in concept systems and terms in terminological systems originating from it is the largest in natural sciences. A linguistic analysis has shown that the term cell is highly productive in term formation, since the extensive terminological system contains multiword terms with up to twelve components that form nominal phrases with a varied structure. Multi-word terms deviate from the terminological principle of economy, but simultaneously display precision and clarity in the naming of concepts in the complex concept systems of professional fields.
Keywords: concept system; terminological system; terminologisation; semantic extension; nominal phrase; the term cell